2017
DOI: 10.21010/ajtcam.v14i4.25
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ulcerogenic Efficacy and Mechanisms of Edible and Natural Ingredients in Nsaid-Induced Animal Models

Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are a class of the most commonly used medicines and proven to be effective for certain disorders. Some people use NSAIDs on daily basis for preventive purpose. But a variety of severe side effects can be induced by NSAIDs. Studies have shown that edible natural ingredients exhibit preventive benefit of gastric ulcer. This paper reviews the efficacy and safety of edible natural ingredients in preventing the development of gastric ulcer induced by NSAIDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Although the NSAIDs‐induced complications can be largely avoided by the concurrent use of H2 receptor blockers and proton pump inhibitors, their use may still be associated with serious but uncommon adverse effects, including microscopic colitis, eosinophilic esophagitis, galactorrhea, hypergastrinemia, decreased bone density and osteoporosis 4 . On the other hand, previous studies have reported that natural constituents can successfully interfere with the occurrence of peptic ulcers in different animal models of NSAIDs exposure, suggesting the potential use of these products as an alternative remedy for protection against gastric ulcer in chronic NSAIDs‐using individuals 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the NSAIDs‐induced complications can be largely avoided by the concurrent use of H2 receptor blockers and proton pump inhibitors, their use may still be associated with serious but uncommon adverse effects, including microscopic colitis, eosinophilic esophagitis, galactorrhea, hypergastrinemia, decreased bone density and osteoporosis 4 . On the other hand, previous studies have reported that natural constituents can successfully interfere with the occurrence of peptic ulcers in different animal models of NSAIDs exposure, suggesting the potential use of these products as an alternative remedy for protection against gastric ulcer in chronic NSAIDs‐using individuals 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 On the other hand, previous studies have reported that natural constituents can successfully interfere with the occurrence of peptic ulcers in different animal models of NSAIDs exposure, suggesting the potential use of these products as an alternative remedy for protection against gastric ulcer in chronic NSAIDs-using individuals. 5 In recent decades, phytochemicals have been a focus of intense research because they have various health-promoting actions. 6 Soyasaponins are a class of phytocompounds commonly derived from legumes such as soya beans, lentils, and peas.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to overestimate the importance of plant preparations during periods of remission or stabilization of the pathological process, when they act as supportive ones, preventing exacerbations. Taking into account the effectiveness, tolerability and cost-effectiveness, phytotherapeutic drugs are not competing, but complementary to modern pharmacotherapy for the treatment of gastric and duodenal ulcers [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An acute gastric mucosa damage is frequently initiated by alcohol consumption, prolonged use of non-steroidal anti-inflammatory drugs (NSAIDs) and stress-induced mucosal damage 34. Currently, the main clinic treatment for this disease is antisecretory drugs such as histamine type 2 receptor antagonists and irreversible proton pump inhibitors 56. Although effective, long-term use will bring more serious complications and aggravate the condition 7.…”
Section: Introductionmentioning
confidence: 99%